THE IMPACT OF OUTDOOR SPACES ON URBAN STRUCTURE: A CASE STUDY OF MASSINISSA NEW CITY - Djaballah Bani; Layeb Hafid (International Journal of Innovative Technologies in Social Science, 2024)
Outdoor spaces, particularly green areas, play a vital role in urban structure, significantly enhancing quality of life and promoting sustainable environments. Parks and squares encourage social interactions, enrich the city’s aesthetics, reflect local identity, and foster community pride. Despite their im-portance, Algerian cities, especially newer ones like Massinissa, often neglect these spaces, which are frequently poorly planned and overlooked. This lack of proper planning leads to a loss of functionality and the deterioration of public spaces. This research paper focuses on the importance of public and green spaces in urban environments, specifically addressing the challenges Massinissa faces due to poor implementation of urban planning laws, limited resident engagement, and inadequate community participation in the maintenance and development of these areas. To address these issues, the study proposes an urban project aimed at revitalizing green spaces in Massinissa, offering recommendations to improve their management and raise environmental aware-ness among residents. By emphasizing the necessity of integrating well-planned outdoor spaces into urban planning, this research seeks to promote a healthier, more sustainable urban environment for the benefit of the entire community.